Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm trying to find the following indefinite integral: $$ \int \frac{2x dx}{\sqrt{1+x^2}} $$

I have already done it via u-substitution, however, I've been asked to solve it with two methods.

I think I can do it by trig substitution as well, however I'm not sure how to finish.

I know I can substitute $x$ in the square root for $\tan\theta$ by the trig substitution rules, but I'm still a bit confused by the $2x$ in the numerator. Does that go to $2\tan\theta$? And how would I finish this?

share|improve this question
2  
The numerator also has the term $dx$ in it, which must be accounted for when you change variables. If $x=\tan(\theta)$, then $dx=\sec^2(\theta)d\theta$ –  A.E Jul 23 '13 at 15:24
add comment

6 Answers 6

$$\frac{\mathrm{d}}{\mathrm{dx}}\sqrt{1+x^{2}}=\frac{x}{\sqrt{1+x^{2}}}$$

from chain rule. So, you have :

$$ \int \frac{2x}{\sqrt{1+x^{2}}} \: dx = \int \frac{\mathrm{d}}{\mathrm{dx}} 2\sqrt{1+x^{2}}$$

share|improve this answer
add comment

Your substitution is spot on!

$$\int\frac{2\tan\theta\sec^2\theta d\theta}{\sec\theta}$$

Now finish it off!

share|improve this answer
    
The above is true as $dx=d(\tan\theta)=\sec^2\theta d\theta$. You can integrate now. –  Host-website-on-iPage Jul 23 '13 at 15:26
    
Ohh, I see now. Thank you and any other helpers! –  cerdra Jul 23 '13 at 15:36
add comment

You presumably did the obvious substitution $u=1+x^2$, and quickly got the integral. I probably would have let $u^2=1+x^2$, which makes the integration even more trivial, but that's because I don't like square roots a whole lot.

These are the reasonable ways to do the integration. (Or else one can write down the answer without any "steps.") Your problem asks for unreasonable ways. But one might as well not be too unreasonably unreasonable.

The trig substitution $x=\tan t$ has been mentioned elsewhere. It is a standard first-year calculus response when one sees $\sqrt{1+x^2}$.

For some variety, one might like to make the substitution $x=\sinh t$. Then we end up wanting $$\int \frac{2\sinh t \cosh t}{\cosh t}\,dt,$$ that is, the integral of $2\sinh t$. Now it is easy. Just mentioning it because in first-year calculus courses the hyperbolic functions are often unjustly neglected.

share|improve this answer
add comment

let $u=\frac{1}{\sqrt{1+x^2}} , dv =2x dx$ then $v=x^2+1, du= -\frac{1}{2}(2x)(1+x^2)^{-\frac32}$

$$\int \frac{2x dx}{\sqrt{1+x^2}}=(x^2+1)\frac{1}{\sqrt{1+x^2}}+\int(x^2+1)\frac{x}{(x^2+1)^{\frac{3}{2}}}dx$$

Simplifying you get

$$\int \frac{2x dx}{\sqrt{1+x^2}}=\sqrt{x^2+1}+\frac{1}{2}\int \frac{2x dx}{\sqrt{1+x^2}}$$

share|improve this answer
    
A very nice one! One might want to draw explicit attention to the cute trick of making a "non-standard" choice for $v$. –  André Nicolas Jul 23 '13 at 15:57
add comment

Presuming the initial $u$ substitution was for $u = 1+ x^2 \implies du =2x\,dx$ (which of course, is a natural choice!

Then for a second method to integrate: Indeed, using trigonometric substitution is a fine choice.

Put $x = \tan\theta$; then we need also to account for $\,dx$: $\;\;\,dx = \sec^2\theta\,d\theta$, and $2x = 2\tan\theta$.

Now, substitute, and simplify!

$$\begin{align} \int \frac{2x\,dx}{\sqrt{1+x^2}} & = \int \frac{(2\tan\theta)\,(\sec^2\theta\,d\theta)}{\sqrt{1+\tan^2\theta}} \\ \\ & = 2\int \frac{\tan\theta\,\sec^2\theta\,d\theta}{\sqrt{\sec^2\theta}} \\ \\& = 2 \int\frac{\tan\theta\sec^2\theta \,d\theta}{\sec\theta} \\ \\ &= 2\int\tan\theta\sec\theta \,d\theta\tag{$\dagger$}\end{align}$$

Now, recall that $\dfrac{d}{dx}\left(\sec \theta\right) = \tan\theta\cdot \sec\theta$

So this gives us $$ 2\int\tan\theta\sec\theta \,d\theta = 2\sec\theta + C = \frac 2{\cos\theta} + C$$

(Note: one can also "convert" $(\dagger)$ to $$2 \int \dfrac{\sin\theta\,d\theta}{\cos^2 \theta}$$ which, to integrate, we have $$2 \int \dfrac{\sin\theta\,d\theta}{\cos^2 \theta} = 2\int -\frac{d}{d\theta}(-\cos\theta)\left(\cos^{-2}\right)\,d\theta = \dfrac{1}{\cos \theta} + C = 2\sec\theta + C$$ which yield the same result as we obtained earlier.

Perhaps trickiest part here is to remember to "back substitute": given $x = \dfrac x1 = \tan\theta \implies \dfrac 2{\sqrt{1 + x^2}} = \cos\theta \implies \sec\theta = \sqrt{1 + x^2}$

share|improve this answer
add comment

Put $1+x^2=z^2$ and hence $xdx=zdz$ to get $$\int\frac{2x}{\sqrt{1+x^2}}dx=\int\frac{2z}{z}dz=2z+c=2\sqrt{1+x^2}+c$$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.